Masa Depan Epistemologi Islam dalam Ekosistem Artificial Intelligence - T. Wildan (Raudhatun Najah Publisher, 2023)
The development of Artificial Intelligence (AI) has transformed the way humans acquire, manage, and validate knowledge, creating new challenges for the paradigm of Islamic epistemology. This study aims to analyze the concept of Islamic epistemology, examine the impact of knowledge transformation driven by Artificial Intelligence, and formulate a framework for reconstructing Islamic epistemology within the digital ecosystem. The study employs a qualitative approach using library research, analyzed through descriptive-analytical and philosophical methods based on both primary and secondary literature. The findings indicate that Artificial Intelligence has not only transformed the mechanisms of knowledge production and dissemination but has also influenced the authority of knowledge, the validity of information, and human patterns of thinking. Although AI provides greater efficiency and broader access to knowledge, its utilization still requires an epistemological foundation that integrates revelation, reason, and empirical experience as complementary sources of knowledge. This study proposes a reconstruction of Islamic epistemology that integrates the values of tawhid, ethics, and public welfare (maslahah) with the advancement of digital technology, thereby establishing an adaptive knowledge paradigm without compromising the philosophical identity of Islam. These findings are expected to enrich the discourse on Islamic philosophy while providing a conceptual framework for the responsible development and utilization of Artificial Intelligence.